Expression of candidate marker genes of sugar starvation is upregulated in growth-suppressed parthenocarpic cucumber fruit. Novel gene markers for sugar starvation in growth-suppressed cucumber fruit - Tazuke, Akio; Kinoshita, Tsuguki; Asayama, Munehiko (Frontiers in Plant Science, 2023)
To examine the physiological change in the growth suppression and abortion of parthenocarpic cucumber fruit, the expression of candidate marker genes of sugar starvation in relation to growth activity was examined. Fruits that failed to start exponential growth seemed to eventually abort. Hexose concentration of fruits was low in growth-suppressed fruit and increased in normally growing fruit consistent with the vacuolization. The correlation matrix indicated that the transcript levels of the genes, except CsaV3_6G046050 and CsaV3_5G032930, had a highly significant negative correlation with the relative growth rate in fruit length and had highly significant mutual positive correlations, suggesting that the asparagine synthetase gene, Cucumis sativus putative CCCH-type zinc finger protein CsSEF1, C. sativus BTB/POZ domain-containing protein At1g63850-like, CsaV3_3G000800, CsaV3_3G041280, and CsaV3_7G032930 are good markers of sugar starvation in cucumber fruit. The expression of candidate marker genes together with the hexose analysis strongly suggests that severe sugar starvation is occurring in growthsuppressed fruit.